The Yor y los poderes de Manchid - Giraldo Osorio, Mónica Yazmín; Alzate Arango, Samuel; Gaviria Salinas , Michaell Anakin (CON-CIENCIA Y TÉCNICA, 2024)
Una fascinante historia sobre la evolución de la raza humana